Projective self-dual polygons in higher dimensions - Chavez-Caliz, Ana (Advances in geometry, 2023)
This paper examines the moduli space M m , n , k of m -self-dual n -gons in ℙ k . We present an explicit construction of self-dual polygons and determine the dimension of M m , n , k for certain n and m . Additionally, we propose a conjecture that extends Clebsch’s theorem, which states that every pentagon in ℝℙ 2 is invariant under the Pentagram map.
Gesehen am 27.11.2023